1998
DOI: 10.1046/j.1365-2699.1998.00248.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of Spanish and Italian terrestrial small mammal coenoses from different biotopes in Mediterranean peninsular tip regions

Abstract: A comparison of terrestrial small mammal coenoses belonging to nine different biotopes in the tips of the Iberian and Italian peninsulas was carried out using the pitfall trapping method. The influence of both habitat type and peninsular effect on composition of small mammal coenoses was analysed. In Southern Italy, 203 specimens belonging to seven species were trapped: Suncus etruscus (Savi, 1822), Crocidura suaveolens (Pallas, 1811), C. leucodon (Hermann, 1780), Microtus savii (de Selys-Longchamps, 1838), Ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
2

Year Published

2005
2005
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 17 publications
0
20
0
2
Order By: Relevance
“…Since Simpson [1] first proposed the peninsula effect, it has been investigated in more than 80 studies (see [6] for a full review), which encompassed a range of geographic regions [7, 8, 9, 10], taxa, [11, 12] and peninsula types (continental and habitat peninsulas; [11, 13]. However, when reviewing a subset of these, Jenkins & Rinne [14] found that the peninsula effect only explained species richness trends in about half the cases (18 out of 37).…”
Section: Introductionmentioning
confidence: 99%
“…Since Simpson [1] first proposed the peninsula effect, it has been investigated in more than 80 studies (see [6] for a full review), which encompassed a range of geographic regions [7, 8, 9, 10], taxa, [11, 12] and peninsula types (continental and habitat peninsulas; [11, 13]. However, when reviewing a subset of these, Jenkins & Rinne [14] found that the peninsula effect only explained species richness trends in about half the cases (18 out of 37).…”
Section: Introductionmentioning
confidence: 99%
“…Como es de esperar por la situación geográfica de Doñana, la comunidad de micromamíferos se caracteriza por una diversidad específica relativamente baja (Cagnin et al 1998). A pesar de ello, y de las lagunas temporales de datos, nuestros resultados reflejan claramente una pérdida importante de diversidad y un llamativo empobrecimiento de la comunidad, tal y como se había sugerido en un estudio reciente (Moreno & Rouco 2013).…”
Section: Discussionunclassified
“…Savi's pine vole also occurs in urban areas, but it avoids too hard, dry and rocky soil, preferring deep, moist and well‐drained soil . However, it may also inhabit sandy soils, peat, clay and soils subject to water logging .…”
Section: Savi's Pine Volementioning
confidence: 99%
“…20 Savi's pine vole also occurs in urban areas, but it avoids too hard, 8 dry and rocky soil, preferring deep, moist and well-drained soil. 23,26,27 However, it may also inhabit sandy soils, peat, clay and soils subject to water logging. 22 Savi's pine vole has a polyphasic daily activity rhythm, alternating short rest and activity periods during both day and night.…”
Section: Distribution and Habitatmentioning
confidence: 99%